GENE-31. DETECTION OF MGMT PROMOTER METHYLATION LEVELS WITH MS-HRM IN PATIENTS WITH GLIOBLASTOMA - Yamashita, Shinji (Neuro Oncol, 2017)
The methylation status of O(6)-methylguanine-DNA methyltransferase (MGMT) gene promoter is not only the predictive marker in adult glioblastoma multiforme (GBM) but also acts as an information useful for clinical decision-making in elderly patients with GBM. Although pyrosequencing analysis has been introduced as the gold standard for evaluating the methylation status of MGMT, many institutions and studies still employ methylation-specific polymerase chain reaction (MSP) since this method is cost-effective and does not require special analyzers. Although MSP shows good correlation with the prognosis of GBM patients treated with Stupp protocol, it has some limitations, such as ambiguity in judgment and non-applicability for evaluating heterogeneously methylated samples. In this study, we focused on the methylation-sensitive high-resolution melting (MS-HRM) for an alternative to MSP. The methylation levels of 6 glioma cell lines were estimated by MS-HRM, and the data was validated by the bisulfite sequencing of cloned alleles, which is another gold standard for quantitatively evaluating methylation levels. Strong correlation was observed between MS-HRM and bisulfite sequencing, indicating that MS-HRM could be a reliable method for estimating methylation levels (Correlation coefficient for #1 primer: 0.959 and #2 primer: 0.960). Methylation levels of 75 samples from patients with GBM were estimated using MS-HRM and compared to that of the MSP data. MS-HRM is superior to MSP in discriminating between responders and non-responders to temozolomide (TMZ) (p value of log-rank test, PFS; MS-HRM: 0.00023, MSP: 0.0035, OS; MS-HRM: 0.00019, MSP: 0.00028). Taken together, our study suggests that MS-HRM is a superior method for detecting MGMT promoter methylation status as compared to MSP.